An Architecture for Verification of Access Control Policies With Multi Agent System Ontologies - Tekbacak, Fatih; Tuğlular, Tuğkan; Tuğlular, Tuğkan; Dikenelli, Oğuz (Institute of Electrical and Electronics Engineers Inc., 2009)
Multi-agent systems (MAS) which communicate with intra-domain and inter-domain agent platforms have access control requirements. Instead of a central mechanism, a fine-graned access control mechanism could have been applied to MAS platforms. This paper emphasizes MAS-based domain and security ontologies with XACML-based access control approach for MAS platforms. The domain dependent behaviour and access control parameters in agent ontologies could be combined within a common XACML policy document that is used through different MAS applications. Agent-based access control requirements and common XACML policy documents should be consistent to enforce policies for MAS. To obtain this condition, the translation of organizational policies and platform based policies have to be considered in detail and the verified policy features have to be enforced in MAS to provide access for resources.
33rd Annual IEEE International Computer Software and Applications Conference, COMPSAC 2009; Seattle, WA; United States; 20 July 2009 through 24 July 2009
Keywords: Access control; Agent based; Ontology; MAS applications; Word processing